Status and gaps of research on respiratory disease pathogens of swine in Africa - Oba, Peter; Wieland, Barbara; Mwiine, F.N.; Erume, J.; Gertzell, E.; Jacobson, M.; Dione, Michel M. (Springer, 2020)
Over the last two decades, the pig population in Africa has grown rapidly, reflecting the increased adoption of pig production as an important economic activity. Of all species, pigs are likely to constitute a greater share of the growth in the livestock subsector. However, constraints such as respiratory infectious diseases cause significant economic losses to the pig industry worldwide. Compared to industrialized countries, the occurrence and impacts of respiratory diseases on pig production in Africa is under-documented. Hence, knowledge on prevalence and incidence of economically important swine respiratory pathogens in pigs in Africa is necessary to guide interventions for prevention and control. The purpose of this review was to document the current status of research on five important respiratory pathogens of swine in Africa to inform future research and interventions. The pathogens included were porcine reproductive and respiratory syndrome virus (PPRSv), porcine circovirus 2 (PCV2), Mycoplasma hyopneumoniae (M. hyopneumoniae), Actinobacillus pleuropneumoniae (APP) and swine influenza A viruses (IAV). For this review, published articles were obtained using Harzing’s Publish or Perish software tool from GoogleScholar. Articles were also sourced from PubMed, ScienceDirect, FAO and OIE websites. The terms used for the search were Africa, swine or porcine, respiratory pathogens, M. hyopneumoniae, APP, PCV2, PPRSv, IAV, prevention and control. In all, 146 articles found were considered relevant, and upon further screening, only 85 articles were retained for the review. The search was limited to studies published from 2000 to 2019. Of all the studies that documented occurrence of the five respiratory pathogens, most were on IAV (48.4%, n = 15), followed by PCV2 (25.8%, n = 8), PPRSv (19.4%, n = 6), while only one study (3.2%, n = 1) reported APP and M. hyopneumoniae. This review highlights knowledge and information gaps on epidemiologic aspects as well as economic impacts of the various pathogens reported in swine in Africa, which calls for further studies.